Naringenin, a citrus flavanone, enhances browning and brown adipogenesis: Role of peroxisome proliferator-activated receptor gamma - Bae, Jiyoung; Yang, Yang; Xu, Xinyun; Flaherty, Jamie; Overby, Haley; Hildreth, Kelsey; Chen, Jiangang; Wang, Shu; Zhao, Ling (Frontiers in Nutrition, 2022)
Identifying functional brown adipose tissue (BAT) has provided new hope for obesity treatment and prevention. Functional BAT includes classical BAT and brown-like adipose tissue converted from white adipose tissue. By promoting thermogenesis (i.e., heat production) via uncoupling protein 1 (UCP1), functional BAT can increase energy expenditure and aid obesity treatment and prevention. Naringenin (NAR) is a flavanone primarily found in citrus fruits. NAR has been reported to decrease body weight, increase energy expenditure in treated mice, and promote browning in human adipocytes. Here, we examined the effects of NAR on 3T3-L1 adipocytes’ browning and β-adrenergic agonist isoproterenol (ISO)-stimulated thermogenic activation and classical murine brown adipogenesis. In addition, we demonstrated the signaling pathways and involvement of peroxisome proliferator-activated receptor gamma (PPARγ) in the process. We found that NAR did not increase Ucp1 mRNA expression at the basal (i.e., non-ISO stimulated) condition. Instead, it enhanced Ucp1 and Pgc-1α up-regulation and thermogenesis under ISO-stimulated conditions in 3T3-L1 adipocytes. NAR promoted protein kinase A (PKA) activation and phosphorylation of p38 MAPK downstream of ISO stimulation and activated PPARγ. Pharmacological inhibition of either PKA or p38 and PPARγ knockdown attenuated Ucp1 up-regulation by NAR. Moreover, NAR promoted brown adipogenesis by increasing lipid accumulation, brown marker expression, and thermogenesis in murine brown adipocytes, which was also attenuated by PPARγ knockdown. Together, our results suggest that NAR may promote the development of functional BAT in part through PPARγ activation. NAR’s role in combating human obesity warrants further investigation.